1999
DOI: 10.1175/1520-0469(1999)056<1197:peaeca>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Polygonal Eyewalls, Asymmetric Eye Contraction, and Potential Vorticity Mixing in Hurricanes

Abstract: Hurricane eyewalls are often observed to be nearly circular structures, but they are occasionally observed to take on distinctly polygonal shapes. The shapes range from triangles to hexagons and, while they are often incomplete, straight line segments can be identified. Other observations implicate the existence of intense mesovortices within or near the eye region. Is there a relation between polygonal eyewalls and hurricane mesovortices? Are these phenomena just curiosities of the hurricane's inner-core circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
464
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(506 citation statements)
references
References 61 publications
40
464
2
Order By: Relevance
“…The radial outflow that was modified by the mesovortices transported the high e air from the eye into the eyewall, and consequently the convective activities in the eyewall were enhanced there. The horizontal distribution of the PV showed the wave-like pattern near the eyewall, which was quite similar to the ideal numerical experiments of Schubert et al (1999) and Kossin and Schubert (2001).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The radial outflow that was modified by the mesovortices transported the high e air from the eye into the eyewall, and consequently the convective activities in the eyewall were enhanced there. The horizontal distribution of the PV showed the wave-like pattern near the eyewall, which was quite similar to the ideal numerical experiments of Schubert et al (1999) and Kossin and Schubert (2001).…”
Section: Resultssupporting
confidence: 83%
“…After t=53h30m, the positive PV anomalies collapsed in the westward side, and the PV increased inside of the eyewall. These results are quite similar to Schubert et al (1999) and Kossin and Schubert (2001). They indicated that the reversal of the radial PV gradient near the eyewall set the stage for dynamic instability and rearrangement of the PV distribution in the barotropic model.…”
Section: Structure Of the Simulated Mesovorticessupporting
confidence: 79%
See 1 more Smart Citation
“…Complete breakdown of the eyewall is not observed, however (cf. Schubert et al, 1999). The evolution is consistent with the picture of propagating near-discrete and sheared vortex Rossby waves and localized mixing events between the eyewall and its interior and exterior.…”
Section: Sensitivity Experimentssupporting
confidence: 80%
“…Weaker secondary circulation and convergence at low level is less conducive to tempering the shear instability associated with the vorticity ring (Nolan, 2001;Montgomery et al, 2002). As a result, redistribution of vorticity along the radial direction could be expected (Schubert et al, 1999;Kossin and Schubert, 2001) and the radial profile of vorticity outside the eyewall was broadened (see black solid line in Figure 6). According to the beta-skirt axisymmetrization hypothesis Figure 6.…”
Section: Intensity and Structurementioning
confidence: 99%